High-Level Modeling of Building Structure Using Octogonal Castellated Beam and Steel Plate Shear Wall System (SPSW) - Ridwan Dwi Setiawan; Koespiadi Koespiadi (NAROTAMA UNIVERSITY, Indonesia)
In reality, the development of a city or region is realized in the form of high-rise buildings. In the world of construction usually planner or executor of a project generally choose between two such material is steel or concrete. Concrete is a construction material that forms most often for current construction projects. In this thesis is exemplified how to choose the steel material in construction. steel profile is quite popular to use the castellated profile, by adding a steel plate shear wall (steel plate shear wall). The result of this structural modeling for building a dental hospital in Malang, get the dimensions of the roof joists with spans7.2 m on the roof using WF profile 300 x 150 x 6.5 x 9 and on the floor with the original profile WF 300 x 200 x 8 x 14, then converted into a castellated beam profile octogonal 442.5 x 200 x 8 x 14. The dimensions of the transverse roof beam using a profile castellated beam octogonal 427.5 x 200 x 8 x 12 and longitudinal roof beam using octogonal profile castellated beam 570 x 200 x 8 x 13. b. Dimensions of the transverse floor beam profile using a profile octogonal castellated beam 427.5 x 200 x 8 x 12 and beam elongated floor using octogonal profile castellated beam 617.5 x 300 x 10 x 15. The dimensions of the column using a 1-4 floor King Cross profile 588 x 300 x 12 x 20, the dimensions of the floor columns 5-7 using a profile King Cross 450 x 200 x 9 x 14.